Prevalence of vitamin D deficiency and the effect of anthropometric and lifestyle factors on vitamin D status in healthy women residing in Riyadh - Binobead, Manal Abdulaziz; Al-Qahtani, Wahidah Hazzaa; Al Bader, Nawal Abdullah; AlSedairy, Sahar Abdulaziz; Arzoo, Shaista (Progress in Nutrition, 2019)
Objective: Hypovitaminosis D is a global health issue, and its increasing prevalence affects people of all ages. This study aimed to determine the vitamin D statuses of healthy women residing in Riyadh, based on measured serum calcidiol (25(OH)2D3) levels and to assess the effects of demographic, anthropometric, and lifestyle factors on vitamin D status. Method: A structured questionnaire was designed and completed after patient consent acquisition to obtain demographic, anthropometric, and lifestyle information. A food frequency questionnaire was used to assess dietary intake, and an immunoassay was used to determine serum vitamin D levels. Result: The mean age of the participants was 33.46 years, and approximately 56% of the participants reported no exposure to sunlight. Only 26.98% of the participants had a normal body mass index (BMI), and 42.86% of the participants had a waist circumference <80 cm. Approximately 86% of the participants were identified as vitamin D deficient (mean, 22.73 nmol/L), and only 7.94% had a normal vitamin D concentration (mean, 96.34 nmol/L) with a cutoff value of 50 nmol/L (for deficiency). A highly significant difference (p≤0.05) was found between the means of various vitamin D status groups. Regarding BMI, the difference in vitamin D levels was highly significant (p≤0.05). There was a strong, positive, and highly significant (p≤0.05) correlation between BMI and waist circumference and a negative (or inverse) correlation between BMI and vitamin D and between waist circumference and vitamin D. The participants’ diets were found to be deficient in vitamin D-rich foods. Conclusion: Education to enhance awareness of the importance of vitamin D is needed, and vitamin D supplementation apart from adequate sun exposure and suitable dietary intake is suggested for individuals with serum calcidiol 25(OH)2D3 levels below 50 nmol/L.